2016
DOI: 10.1063/1.4946884
|View full text |Cite
|
Sign up to set email alerts
|

Transparent ferrimagnetic semiconducting CuCr2O4 thin films by atomic layer deposition

Abstract: We report the magnetic and optical properties of CuCr2O4 thin films fabricated by atomic layer deposition (ALD) from Cu(thd)2, Cr(acac)3, and ozone; we deposit 200 nm thick films and anneal them at 700 °C in oxygen atmosphere to crystallize the spinel phase. A ferrimagnetic transition at 140 K and a direct bandgap of 1.36 eV are determined for the films from magnetic and UV-vis spectrophotometric measurements. Electrical transport measurements confirm the p-type semiconducting behavior of the films. As the ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The XRD patterns of the pristine and modified CuCr 2 O 4 nanoparticles have been shown in Figure . In both bare and modified CuCr 2 O 4 patterns, the diffraction peaks at 2 θ = 28.94, 30.43, 34.45, 36.88, 41.58, 55.43, 60.77, and 64.20 were assigned to the (200), (112), (211), (202), (220), (321), (400), and (224) crystal planes, which confirmed that the crystal structure of CuCr 2 O 4 nanoparticles have been fully formed based on the JCPDS [01‐072‐1212] standard cart with tetragonal crystal system . Moreover, alongside beside the prepared CuCr 2 O 4 nanoparticles, both (012) and (104) phases were related to the rhombohedral structure of constructed CrCuO2.…”
Section: Resultsmentioning
confidence: 66%
“…The XRD patterns of the pristine and modified CuCr 2 O 4 nanoparticles have been shown in Figure . In both bare and modified CuCr 2 O 4 patterns, the diffraction peaks at 2 θ = 28.94, 30.43, 34.45, 36.88, 41.58, 55.43, 60.77, and 64.20 were assigned to the (200), (112), (211), (202), (220), (321), (400), and (224) crystal planes, which confirmed that the crystal structure of CuCr 2 O 4 nanoparticles have been fully formed based on the JCPDS [01‐072‐1212] standard cart with tetragonal crystal system . Moreover, alongside beside the prepared CuCr 2 O 4 nanoparticles, both (012) and (104) phases were related to the rhombohedral structure of constructed CrCuO2.…”
Section: Resultsmentioning
confidence: 66%